2020
DOI: 10.1103/physreve.101.012216
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the ratio of two consecutive level spacings in orthogonal to unitary crossover ensembles

Abstract: The ratio of two consecutive level spacings has emerged as a very useful metric in exploring universal features exhibited by complex spectra. It does not require the knowledge of density of states and is therefore quite convenient to compute in studying the spectrum of a general system. The Wigner surmise like results for the ratio distribution are known for the invariant classes of Gaussian random matrices. However, for the crossover ensembles, which are useful in modeling systems with partially broken symmet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Prior studies on real and complex spacing ratios arising from Hermitian and non-Hermitian systems, respectively, have shown that such measures are able to distinguish between integrable and chaotic spectra, see e.g. [22,[43][44][45]. Here we showed that the same quantities can also differentiate the disconnected phase ( k < 1), in which the directed network is divided into several small components, and the phase ( k > 1), giant component connecting the majority of the emerges.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on real and complex spacing ratios arising from Hermitian and non-Hermitian systems, respectively, have shown that such measures are able to distinguish between integrable and chaotic spectra, see e.g. [22,[43][44][45]. Here we showed that the same quantities can also differentiate the disconnected phase ( k < 1), in which the directed network is divided into several small components, and the phase ( k > 1), giant component connecting the majority of the emerges.…”
Section: Discussionmentioning
confidence: 99%
“…One way to avoid the problem of unfolding is by using the idea of the ratio of two consecutive level spacings which is independent of the local density of states, and it does not require unfolding [44,[65][66][67][68][69]].…”
Section: Proposed Studymentioning
confidence: 99%
“…The distribution intermediate of Poisson and GOE is described by Brody distribution [27]. Recently, intermediate semi-poissonian statistics [28] and crossover random matrix ensembles [29] are also reported. Going beyond this, recently, the distribution of the closest neighbor (CN) spacing, s CN and farther neighbor (FN) spacing, s F N from a given level are introduced [30].…”
Section: Introductionmentioning
confidence: 99%